Does customer trust play a mediating role between salesperson competence and performance? - Dong-jenn Yang; Meng J. Wu (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
The questions of what competence constitutes in salesperson performance and why it does matter are important issue of marketing and sales management. This study examined the importance of competence in a salesperson's performance and the mechanism underlying the relationship between competence and performance. We used multiple sources to collect data from 165 sales agents working in a life insurance company and 338 customers at two time points. The results demonstrated that the mediation of the effect of social and professional competence on objective salesperson performance differed depending on affective trust and cognitive trust.
Keywords: M31; M37; 330; Social competence; professional competence; cognitive trust; affective trust; salesperson performance